Learn by distance: advice for choosing an effective and inclusive e- Learning platform - Dario Ianes; Leonardo Venturoso (IUL Research)
In this last eventful year, in order to deal with the health emergency, the logistic problems related to it and the imposition of "distance learning", digital e-Learning platforms and tools have been widely used both for teaching and for autonomous work. However, these technologies were often completely new to users and their parents, who had to quickly adapt to the situation by learning how to handle them, not always in the most efficient way. Moreover, many families were not technologically and economically prepared for this situation due to inadequate internet connection, equipment and related tools (Beaunoyer E. 2020, Van Lancker, W. 2020).